Enhanced antimicrobial, antioxidant, in vivo antitumor and in vitro anticancer effects against breast cancer cell line by green synthesized un-doped SnO2 and Co-doped SnO2 nanoparticles from Clerodendrum inerme. (December 2018) - Khan, Shakeel Ahmad; Kanwal, Sadia; Rizwan, Komal; Shahid, Sammia
Abstract: A novel approach was employed for the synthesis of un-doped tinoxide and Cobalt-doped tinoxide (Co-doped SnO2 ) nanoparticles (NAPs) by using aqueous extract of Clerodendrum inerme with the help of eco-friendly superficial solution combustion method. Synthesized NAPs were characterized by different spectroscopic techniques and results from XRD, TEM, SEM, EDX and UV–Vis examines confirmed the successful synthesis, crystalline nature and spherical structure of un-doped SnO2 and Co-doped SnO2 NAPs with the average grain size of 30 and 40 nm; and band gap energy of 3.68 and 2.76 eV respectively. Antimicrobial propensity of the synthesized NAPs was determined by agar well assay, SEM, TEM and confocal laser scanning microscopic analysis against various bacterial and fungal strains. Synthesized Co-doped SnO2 NAPs were unveiled the extraordinary antibacterial and antifungal activities against E. coli, B. subtilis, A. niger, A. flavus, and C. albicans with the zone of inhibitions of 30 ± 0.08 mm and 26 ± 0.06 mm, 17 ± 0.04 mm, 23 ± 0.08 mm and 26 ± 0.06 respectively which were also evidenced from SEM, TEM and confocal laser scanning microscopy. In addition, green synthesized Co-doped SnO2 NAPs were demonstrated the substantial antioxidant activity by scavenging DPPH, significant in vitro anticancer and in vivo antitumor activity on breast carcinoma cells (MCF-7) and Ehrlich ascites tumor cell lines respectively than standard. The hemolytic activity disclosed low cytotoxicity of fabricated NAPs (0.89 ± 0.05%) at 5 mg/mL, which was indicated their biocompatibility potential. Hence, the multi-purpose properties of synthesized NAPs presented in the current study can be further deliberated for pharmaceutical and nanomedicine applications. Graphical abstract: Highlights: Un-doped SnO2 and Co-doped SnO2 were synthesized by green approach. They were synthesized using solution combustion method in which leaves extract of C. inerme act as a fuel. Synthesized Co-doped SnO2 possess potent and enhanced antibacterial, antifungal, and anticancer properties. Biological activities are directly linked to the physical characteristics of synthesized nanoparticles. The results indicate that Co-doped SnO2 will prove good candidates for future therapeutic applications.